Church Management in the Organic Church Paradigm: Integrating Spiritual Structure and Ministry Governance - Christian Eko Wior (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
Organic church and church management are often viewed as two opposing approaches: one emphasizes spiritual vitality and relational community life, while the other focuses on structure, planning, and organizational sustainability. This study argues that these approaches need not be placed in tension; rather, they can be integrated into a coherent and holistic framework of ministry. Using a descriptive qualitative approach through literature analysis, this research explores how the concept of the organic church in New Testament ecclesiology can be integrated with key principles of modern church management. Insights from Bonhoeffer (1954) on communal life, Erickson (1998) on the nature of the body of Christ, and Tomatala (2014) on congregational development provide the foundational basis for this integrative model. The findings indicate that the organic church contributes life, relational depth, and the dynamic work of the Holy Spirit, whereas church management offers direction, coordination, and the structural space needed for spiritual gifts to function. Together, these dimensions produce a living structure that is flexible, relational, theological, and accountable. The study concludes that the contemporary church requires structures that support life rather than replace it.